The role of market discipline in handling problem banks - David T. Llewellyn; David G. Mayes (Bank of Finland, 2003)
This paper considers the conditions that are necessary for market discipline to complement prompt corrective action (PCA) by the authorities in handling problem banks.We initially consider precisely what market discipline means in this context, who exercises it and the preconditions that are necessary for it to operate effectively.We explore the incentives that are necessary for PCA and market discipline to reinforce rather than cancel each other and in particular consider the limits to market discipline in this context from corporate governance and from difficulties in valuation.While our analysis is primarily aimed at advanced countries, we also examine problems in emerging markets and how deposit insurance arrangements might conflict with the aims of both PCA and market discipline.
URN:NBN:fi:bof-20140807581
Keywords: 330; market discipline; banks; prompt corrective action